A Meditation on Mediation: Evidence That Structural Equations Models Perform Better Than Regressions - Iacobucci, Dawn; Saldanha, Neela; Deng, Xiaoyan (Journal of Consumer Psychology, 2007)
In this paper, we suggest ways to improve mediation analysis practice among consumer behavior researchers. We review the current methodology and demonstrate the superiority of structural equations modeling, both for assessing the classic mediation questions and for enabling researchers to extend beyond these basic inquiries. A series of simulations are presented to support the claim that the approach is superior. In addition to statistical demonstrations, logical arguments are presented, particularly regarding the introduction of a fourth construct into the mediation system. We close the paper with new prescriptive instructions for mediation analyses.